1999
DOI: 10.1046/j.1432-1327.1999.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of 1,2‐dieicosapentaenoyl‐sn‐glycero‐3‐phosphocholine in Caenorhabditis elegans

Abstract: Previously, we showed that lowering the growth temperature increased the level of eicosapentaenoic acid (EPA) in the phosphatidylcholine (PtdCho) of Caenorhabditis elegans. In this study, we investigated the molecular species composition of PtdCho of C. elegans, with an emphasis on EPA-containing species. C. elegans contained a substantial amount of 1,2-dipolyunsaturated fatty acid-containing PtdCho (1,2-diPUFA-PtdCho) species, such as arachidonic acid/EPA and EPA/EPA, which are unusual phospholipids in higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The source of vaccenic acid, dietary or de novo synthesis, that becomes incorporated in the longer second phase is not known, but its significance might be in substituting for 20:5(n-3) in the sn-1 position of di-20:5(n-3) PC. This is an unusual complex lipid that has been found in C. elegans and whose level is enhanced in long-term 15°C-reared worms compared with 25°C-reared worms (35). We found that 3 ablation by RNAi elicited no change in the cold tolerance phenotype (data not shown), suggesting that the proportion of 20:5(n-3) was not critical to cold tolerance and that other less unsaturated PUFAs can substitute.…”
Section: Discussionmentioning
confidence: 72%
“…The source of vaccenic acid, dietary or de novo synthesis, that becomes incorporated in the longer second phase is not known, but its significance might be in substituting for 20:5(n-3) in the sn-1 position of di-20:5(n-3) PC. This is an unusual complex lipid that has been found in C. elegans and whose level is enhanced in long-term 15°C-reared worms compared with 25°C-reared worms (35). We found that 3 ablation by RNAi elicited no change in the cold tolerance phenotype (data not shown), suggesting that the proportion of 20:5(n-3) was not critical to cold tolerance and that other less unsaturated PUFAs can substitute.…”
Section: Discussionmentioning
confidence: 72%
“…Ptdcholine concentration was found to be correlated with increased FT among 13 hardened wheat cultivars (Horváth et al, 1980). It is interesting to note that in C. elegans, where homologs of the wheat WPEAMT have been identified, LT treatment increases the level of several types of phosphatidylcholines (Tanaka et al, 1999). This finding suggests that nematodes and plants may share a common pathway for Ptd-choline biosynthesis.…”
Section: Table I In Vitro Phospho-base N-methyltransferase Activitiesmentioning
confidence: 93%
“…The assay was conducted as described previously [29]. Each incubation contained 32 nmol of 1‐acyl‐2‐lyso‐PtdCho or 1‐acyl‐2‐lyso‐PtdIns, 0.5 m m nicotinamide, 1.5 m m glutathione, 0.15 m KCl, 5 m m MgCl 2 , 0.25 m sucrose, 3.0 m m ATP, 0.1 m m CoA, 50 m m potassium phosphate buffer (pH 7.4), 0.2 mg protein of the microsomal fraction of HepG2 cells, and 50 nmol of fatty acid in a total volume of 1.0 mL.…”
Section: Methodsmentioning
confidence: 99%